2019
DOI: 10.1523/jneurosci.1317-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Light-Activated ROS Production Induces Synaptic Autophagy

Abstract: The regulated turnover of synaptic vesicle (SV) proteins is thought to involve the ubiquitin-dependent tagging and degradation through endo-lysosomal and autophagy pathways. Yet, it remains unclear which of these pathways are used, when they become activated, and whether SVs are cleared en masse together with SV proteins or whether both are degraded selectively. Equally puzzling is how quickly these systems can be activated and whether they function in real-time to support synaptic health. To address these que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 92 publications
0
46
0
Order By: Relevance
“…Indeed, we observed in our experimental setup that BCN-1, LC3, and Lamp-2 were significantly upregulated by elevated CRH levels in neurons (in vitro and in vivo) and that signs of autophagy induction, especially in the presynaptic compartment, appeared. Interestingly, recent evidence of fine-tuned protein homeostasis regulated by autophagy at synapses, especially in the presynaptic compartment, was reported [71][72][73]. We found that CRHR1 activation was correlated with the rapid downregulation of (presynaptic) BDNF and that BDNF degradation was rescued by CRHR1 blockage as well as NF-κB pathway inhibition.…”
Section: Discussionmentioning
confidence: 54%
“…Indeed, we observed in our experimental setup that BCN-1, LC3, and Lamp-2 were significantly upregulated by elevated CRH levels in neurons (in vitro and in vivo) and that signs of autophagy induction, especially in the presynaptic compartment, appeared. Interestingly, recent evidence of fine-tuned protein homeostasis regulated by autophagy at synapses, especially in the presynaptic compartment, was reported [71][72][73]. We found that CRHR1 activation was correlated with the rapid downregulation of (presynaptic) BDNF and that BDNF degradation was rescued by CRHR1 blockage as well as NF-κB pathway inhibition.…”
Section: Discussionmentioning
confidence: 54%
“…Distally formed autophagosomes mature during their retrograde axonal transport (Guedes-Dias and Holzbaur, 2019; Stavoe and Holzbaur, 2019) prior to their fusion with degradative lysosomes enriched in proximal axons and in neuronal somata (Hill and Coló n-Ramos, 2020;Maday and Holzbaur, 2014;Maday et al, 2012). In addition to this largely constitutive process of neuronal autophagy (Maday and Holzbaur, 2016), formation of autophagosomes has been suggested to be facilitated by mitochondrial damage (Ashrafi et al, 2014), neuronal activity (Shehata et al, 2012;Wang et al, 2015), overexpression of aggregation-prone proteins (Corrochano et al, 2012), reactive oxygen species (ROS)-induced protein oxidation (Hoffmann et al, 2019), or genetic depletion of key AZ proteins (Okerlund et al, 2017). We demonstrate, using knockout mice conditionally lacking the essential autophagy protein ATG5 and quantitative proteomics, that loss of neuronal autophagy causes selective accumulation of tubular ER in axons, resulting in increased excitatory neurotransmission because of elevated calcium release from ER stores via ryanodine receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Whether SV cycling and synaptic autophagy are reciprocally regulated and how they crosstalk with somatic autophagy is a matter of investigation. In a recent article, selective induction of autophagy at the presynaptic site has been shown to specifically target damaged proteins, thus maintaining synapse integrity and function (Hoffmann et al, 2019). The discovery that neuronal autophagy and formation of APs at synapses are activity dependent (Shehata et al, 2018) suggests that synaptic autophagy may be regulated by long-term synaptic plasticity underlying learning and memory formation.…”
Section: Autophagy and Synaptic Functionmentioning
confidence: 99%